The Moorean argument for the full moral status of those with profound intellectual disability: a rejoinder to Roberts. Issue 4 (10th March 2016) - Curtis, Benjamin; Vehmas, Simo
Abstract : In a recent paper we argued that a Moorean strategy can be employed to justify our continuing to believe the following proposition, even in the presence of philosophical views that entail it is false, without any philosophical argument against those views, and without any positive philosophical argument in its favour: H>A: Humans have an equal moral status that is higher than the moral status of non-human animals. The basic idea is that our confidence in the truth of this proposition is greater than our confidence in the propositions that make up those philosophical views that entail that it is false, and that this is sufficient to justify rejecting those views and to continue to believe H>A. Roberts has recently responded to our argument by claiming that (i) although the Moorean strategy is valid, it is not powerful and (ii) a resort to the Moorean strategy reflects too great a pessimism about the accounts available that purport to justify H>A. In this short rejoinder we explain why Roberts fails to establish his two claims.